Health Claim Regulation and Public Health: Individual Choice or Libertarian Paternalism? - Todt, Oliver; Luján, José Luis (Teorema, 2021)
We present an interpretation of the current debate in the field of health claim regulation with respect to public health and standards of proof. Health claims are scientifically validated statements regarding the health benefits that a food may confer upon its consumers. We argue that the methodological debates in health claim regulation conceal a very different debate, related to who takes the decisions about consumption of foods with health claims: individual consumers or (at least partially) regulators. Our analysis reveals two opposing stances: one which on our interpretation is compatible with libertarian paternalism, and the other focused on individual choice on the basis of "sound science".